2015
DOI: 10.1007/s00018-015-1962-7
|View full text |Cite
|
Sign up to set email alerts
|

Connexin and pannexin signaling pathways, an architectural blueprint for CNS physiology and pathology?

Abstract: The central nervous system (CNS) is composed of a highly heterogeneous population of cells. Dynamic interactions between different compartments (neuronal, glial, and vascular systems) drive CNS function and allow to integrate and process information as well as to respond accordingly. Communication within this functional unit, coined the neuro-glio-vascular unit (NGVU), typically relies on two main mechanisms: direct cell-cell coupling via gap junction channels (GJCs) and paracrine communication via the extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 384 publications
(563 reference statements)
0
46
0
Order By: Relevance
“…Interestingly, elevated Ca 2+ signal in astrocytes can in turn triggers a cascade of [Ca 2+ ] i ‐dependent pathways including gliotransmitter release. Indeed, ATP and glutamate release associated to HC activity was demonstrated in glial cells reviewed in (Decrock et al, ): for instance in cultured cells, both Panx1 and Cx43 HCs participate to ATP release in microglial cells (Ma et al, ; Orellana, Montero, & von Bernhardi, ) and in astrocytes (Iglesias, Dahl, Qiu, Spray, & Scemes, ; Kang et al, ); also glutamate release associated to Cx HCs involving Cx43 and Cx32 was demonstrated in astrocytes (Ye et al, ) and in microglial cells (Takeuchi et al, ), respectively. Moreover, in acute or chronic pathological situations, sustained activation of HCs can contribute to an excessive release of ATP and/or glutamate with neurotoxic effects that are alleviated by reducing Cx43 expression or function (Bennett et al, ; Schulz et al, ; Takeuchi & Suzumura, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated Ca 2+ signal in astrocytes can in turn triggers a cascade of [Ca 2+ ] i ‐dependent pathways including gliotransmitter release. Indeed, ATP and glutamate release associated to HC activity was demonstrated in glial cells reviewed in (Decrock et al, ): for instance in cultured cells, both Panx1 and Cx43 HCs participate to ATP release in microglial cells (Ma et al, ; Orellana, Montero, & von Bernhardi, ) and in astrocytes (Iglesias, Dahl, Qiu, Spray, & Scemes, ; Kang et al, ); also glutamate release associated to Cx HCs involving Cx43 and Cx32 was demonstrated in astrocytes (Ye et al, ) and in microglial cells (Takeuchi et al, ), respectively. Moreover, in acute or chronic pathological situations, sustained activation of HCs can contribute to an excessive release of ATP and/or glutamate with neurotoxic effects that are alleviated by reducing Cx43 expression or function (Bennett et al, ; Schulz et al, ; Takeuchi & Suzumura, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the possible involvement of pannexin channels also cannot be ignored (Panchin et al, 2000). Multiple studies suggest that these two types of hemichannels have a close relationship and work coordinately in the CNS that differentially regulates the ionic and metabolic fluxes and cellular function (Decrock et al, 2015; Jiang and Penuela, 2016). …”
Section: Connexin Hemichannelsmentioning
confidence: 99%
“…Cx26 is detected at early stages of the development, while Cx32 and Cx43 are expressed throughout entire brain development and adulthood (Nadarajah et al, 1997). After birth, Cxs play important roles in brain functions, coordinating the activity between neurons and also between glial cells (Pereda, 2014; PosÅuszny, 2014; Decrock et al, 2015; Del Rio et al, 2015). Changes in expression levels and/or channel function formed by several different Cxs have been associated with a number of central nervous system (CNS) disorders.…”
Section: Modulation Of Connexins By Mirnasmentioning
confidence: 99%